Effects of pretreatment with phenobarbitone and phenytoin on the pharmacokinetics and toxicity of phenytoin on the pharmacokinetics and toxicity of misonidazole in mice. - Workman, P. (Nature Publishing Group, 1979)
Concentrations of the hypoxic cell radiosensitizer misonidazole (MIS) and its O-demethylated metabolite Ro 05-9963 were determined in plasma (or blood), brain and tumour after injection of 1 g/kg MIS i.p. to control mice or mice pretreated with 4-6 daily injections of phenobarbitone or phenytoin. Analysis was by high-performance liquid chromatography (HPLC). Phenobarbitone and phenytoin did not alter the peak MIS concentration in plasma, brain or tumor. However, the apparent elimination half-life (t 1/2) for MIS was reduced by 20-67%, and the area under the curve (AUC) was decreased by 23-49% in plasma, brain and tumour. The decrease in MIS t 1/2 was associated with an initially increased Ro 05-9963 metabolite concentration. However, the AUC for total 2-nitromidazole (MIS + Ro 05-9963) in plasma, tumour and brain was reduced by 20-50%. Urinary excretion of MIS and its metabolites accounted for 15-42% of the injected dose, and was unaltered by pretreatment with phenobarbitone or phenytoin. Tumour/plasm and brain/plasma concentration ratios for MIS, and tumour/plasma ratios for Ro 05-9963 were very similar, but the brain/tumour ratios for Ro 05-9963 were considerably lower. Tissue/plasma ratios were unaltered by pretreatment with phenobarbitone or phenytoin. The acute LD50 for MIS was increased from 1.54 to 1.90 g/kg after phenobarbitone pretreatment and 1.78 g/kg after phenytoin pretreatment. In addition, pretreatment with either compound shortened the duration of the MIS-induced decrease in body temperature. These data suggest that pretreatment with microsomal-enzyme-inducing agents may reduce the toxicity of MIS without affecting the radiosensitization. The significance of these findings for the mechanism of MIS toxicity is also discussed.